The administrative decision against the protection of ac- quired rights under the provisions of the council of state (comparative study) - Abd Al-Hadi, Maysoon Ali (Opción, 2019)
Administrative decisions issued by the public administration may vary, either in the form of a legal status, amended or revoked, or the administrative decision may be revealing a legal situation, which may be either explicit or implicit, negative or positive, and as a result of these numerous decisions, or may be illegal, thus being subject to appeal and cancellation, provided that they have not established rights for individuals. The abolition should not prejudice the acquired rights to ensure the stability of the legal situation. Illegal administration at Either by itself or through the judiciary, and in front of that we find the emergence of an idea of the admin- istrative decision appeared in Egypt, namely the idea of administrative decision counter (opposite) of the administrative decision of the draft issued by the Author- ity restricted to the administration, the administrative decision counter is a draft decision issued with the same elements and elements that characterize the admin- istrative decision However, it differs from the idea of canceling the administrative decision in that it is legitimate, whereas the cancellation is for the administrative decision, which is legitimate and illegitimate, and differs on the other side from the idea of the administrative drawdown in that the effects of the counter-decision are transferred to the future in contrast to the draw that extends its effects to the past and the future.